PENGARUH HIPERKOLESTROLEMIA TERHADAP FUNGSI KOGNITIF PADA PASIEN LANSIA DI PUSKESMAS SIMALINGKAR MEDAN - Febrin T.Rumapea; Laura O Siagian; Nasib M Situmorang (Universitas Methodist Indonesia, 2024)
Background: of the study. Damage to the structure and function of the brain can lead to a decline and impaired cognitive function. This cognitive impairment can be caused by increasing age and risk factors such as dyslipidemia, hypertension, diabetes and cerebral blood vessels. Methods: This study used a cross-sectional design. The research population is all the elderly who are in the working area of the Simalingkar Health Center in 2022 as many as 500 people. The sample size is 66 people. The sampling technique was carried out using a consecutive sampling technique. Hypercholesterolemia data collection is based on medical record data, while cognitive impairment uses a mini mental status examination questionnaire. Analysis of research data using univariate and bivariate with Chi Square test. Results: showed that the majority of the elderly experienced hypercholesterolemia as many as 50 people (76.9%), and cognitive function in the elderly mostly in the normal category as many as 41 people (56.9%). There was no correlation between hypercholesterolemia and cognitive function in the elderly (p = 0.231 > 0.05). Conclusion: Hypercholesterolemia is not associated with cognitive function in the elderly.